Culture Shock Among Migrant Students and Intervention Strategies: An Islamic Psychological Perspective - Isa, Mas'ud Shidik (UMSU, 2025)
The goal of this study is to conduct a literature evaluation on the effects of culture shock on international students. A descriptive review was employed in this literature study. Secondary data sources were employed in this investigation, including the indexing engines Scopus, Jstore, and Google Scholar. Articles from the recent six years (2018-2024) were chosen for data gathering, and they included both international and national articles. The findings of this literature analysis revealed that of the 151,773 articles discovered by the three indexers, 10 matched the inclusion criteria. The findings revealed that culture shock is a highly widespread phenomenon in all contexts, particularly among international students. Which then Islamic psychology is present as one of the solutions given in handling or reducing the impact of culture shock itself.